Genomic insights and bioconversion potential in the Black Soldier fly (Hermetia illucens) : current advances and future directions - Oliveira, Joana (2026)
The global population continues to rise, placing increasing pressure on the agri-food sector and leading to the accelerated generation of urban organic waste, factors that collectively intensify climate stress and environmental instability. Insects are recognised for their remarkable capacity to transform substrates into valuable products, with the black soldier fly larvae (BSFL) emerging as one of the most efficient and widely utilised species for this purpose. Beyond recycling organic matter, BSFL can also mitigate microbial contamination, effectively reducing bacterial and fungal loads in waste substrates. Understanding and manipulating the genome could provide tools to improve BSFL bioconversion process and contribute to sustainability. In this review, we provide an overview of recent advances in black soldier fly genomics and genome-editing technologies. Although research in this subject remains limited, recent studies have clarified its origin, characterised its genome, and established the foundation for targeted genetic improvements to enhance by-product conversion, nutrient recovery, and environmental sustainability.